Maize responds to Azotobacter sp and Burkholderia sp inoculation at reduced dose of nitrogen fertilizer - Sánchez-Yáñez, Juan Manuel (2014)
The positive maize response to inoculation with plant growth promoting bacteria (PGPB) as Azotobacter sp and Burkholderia sp an endophytic type, are an alternative to reduced and optimize nitrogen fertilizer (NF) dose, recommended for this plant, without adversely affect its growth. The aim of this study was to analyze maize respond to inoculation with Azotobacter sp and Burkholderia sp at the dose 50% of FN. Used an experimental design of randomized blocks. By response variables: percent germination (%), the shoot and root phenology: plant height (PH), root length (RL) and biomass: shoot fresh weight (SFW) and root fresh weight (RFW), the shoot dry weight (SDW) and root dry weight (RDW). The results indicated a positive maize respond to PGPB inoculation at germination, seedling and flowering level, reached a RDW of 7.03 g, statistically significant value compared with 2.60 g of RDW non inoculated maize feed with NF dose recommended regard as relative control (RC). This suggests a synergistic interaction among these PGPB in synthesis of plant growth promoting substances (PGPS) on maize, to optimize the reduced NF dose.